Soil nitrogen recovery and seasonal changes of xylem sap amino acids of Amazonian tree species following pasture abandonment - de Araújo, Vanderlei Borboni Ferreira; Justino, Gilberto Costa; da Silva, Carlos Eduardo Moura; Vera, Saul Alfredo Antezzana; Lins, Lays; Sodek, Ladaslav; de Camargos, Liliane Santos [UNESP]; Pereira, Luis Octávio Vieira; de Carvalho Gonçalves, José Francisco (Springer Nature, 2019)
We conducted this study to understand the dynamics of revegetation by examining the levels of mineral nitrogen (NO3− and NH4+) in soil and the capacity of nitrogen use by the principal species growing in secondary forest in central Amazonia. For this, we measured the nitrate and ammonium content of soil, leaves and xylem sap, nitrate reductase activity of the leaves and free amino acid contents of the xylem sap in five tree species (Vismia cayennensis, Vismia japurensis, Bellucia dichotoma, Laetia procera and Goupia glabra) over a chronosequence during recovery after pasture abandonment at two seasons. Soil ammonium was higher in the dry season and nitrate higher in the wet season and increased these with pasture abandonment age. V. japurensis, B. dichotoma and G. glabra decreased foliar ammonium due to pasture abandonment in the dry season and foliar ammonium increased in L. procera in the wet season. V. japurensis and V. cayennensis showed a decrease in nitrate reductase activity, while B. dichotoma and L. procera showed an increase. Xylem nitrate decreased in L. procera and B. dichotoma in the dry and wet seasons, respectively, and ammonium increased only in V. japurensis and V. cayennensis in the wet. Xylem arginine increased in all plant species after a period of pasture abandonment (except B. dichotoma). Tree species growing in pasture abandoned areas didn’t show the same pattern of use of nitrogen, and this can be important in order to understand the nitrogen metabolism of trees in the Amazon region during forest restoration.
Keywords: Chronosequence; Deforestation; Nitrate reductase; Seasonality of precipitation; Secondary forest